2011
DOI: 10.1002/ss.393
|View full text |Cite
|
Sign up to set email alerts
|

Transition strategies to ensure active student engagement

Abstract: Student affairs professionals have an opportunity to promote active student engagement and improve the experiences of students with disabilities by embracing a collaborative and inclusive model of practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…For instance, faculty who "bring themselves" to the classroom-perhaps sharing personal anecdotes, talking about their own professional histories, and talking with students about their own research interests and activity-help create a connection to students that promotes student success (Vogt 2008). To encourage comfort in seeking out the professor for help, faculty can actively encourage students to come to office hours, or-if time is a concern-can offer group or virtual office hours (Cox et al, 2010;Korbel, McGuire, Banerjee, and Saunders 2011). Indeed, many students, especially those with high levels of course-related anxiety, are reluctant to ask for help (Karabenick 2003), so periodic reminders from faculty that help is available can provide needed encouragement.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, faculty who "bring themselves" to the classroom-perhaps sharing personal anecdotes, talking about their own professional histories, and talking with students about their own research interests and activity-help create a connection to students that promotes student success (Vogt 2008). To encourage comfort in seeking out the professor for help, faculty can actively encourage students to come to office hours, or-if time is a concern-can offer group or virtual office hours (Cox et al, 2010;Korbel, McGuire, Banerjee, and Saunders 2011). Indeed, many students, especially those with high levels of course-related anxiety, are reluctant to ask for help (Karabenick 2003), so periodic reminders from faculty that help is available can provide needed encouragement.…”
Section: Discussionmentioning
confidence: 98%
“…President Barack Obama suggested that the United States increase the number of college graduates by 8 million by the year 2020, noting that the country has fallen from number 1 to number 12 in college graduation rates in a single generation (Korbel, McGuire, Banerjee, & Saunders, 2011). Many higher education institutions are actively recruiting students with disabilities as a source of revenue to maintain or increase enrollments (Mangrum & Strichart, 1988).…”
Section: Individuals With Autism Spectrum Disorder Entering Collegementioning
confidence: 99%
“…The types of disabilities that are presenting themselves in the college sector have changed dramatically and now include students with psychiatric disorders, chronic health conditions, autism spectrum disorders, and severe food and environmental allergies (U.S. Government Accountability Office, 2009). These students will have different needs and goals and may benefit from employment training and other services not traditionally provided by universities (Korbel et al, 2011).…”
Section: Individuals With Autism Spectrum Disorder Entering Collegementioning
confidence: 99%
See 2 more Smart Citations